Cladistic analysis finds a placement for an enigmatic species, Peyerimhoffia sepei sp. n. (Diptera: Sciaridae), with a note on its spermatophore - Hippa, Heikki; Vilkamaa, Pekka (Zootaxa, 2005)
A new species of Sciaridae from northern Europe, with an exceptional combination of characters, is placed in the phylogenetic system of the family by a cladistic analysis. The new species, Peyerimhoffia sepei sp. n., is described and illustrated, and the spermatophores of Sciaridae are briefly discussed.